RELATIVE STABILITY MARGINS OF MULTIVARIABLE SYSTEMS - CHARACTERISTIC LOCUS APPROACH - Cameron, R; Kouvaritakis, B (1979)
Recent work has proven that characteristics locus plots form the natural medium for the generalization of the Nyquist approach. In the present paper these plots are used to extend classical scalar techniques of assessing relative stability margins to the multivariable case. Thus the estimation of closed-loop poles using curvilinear squares is first discussed and subsequently the use of constant dynamic magnification circles in predicting performance under feedback is considered. A new concept relevant to both techniques is introduced, namely that of interference. Interference relates to the loop distribution of eigenvalues, and complements the concept of interaction which relates to eigenvector distribution.